2010
DOI: 10.1002/er.1717
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of laminar flow development with heat and mass transfer in PEM fuel cell flow channels having oxygen and hydrogen suction at one channel wall

Abstract: SUMMARYNumerical simulation has been carried out of the fluid flow, heat and mass transfer for the developing laminar flow in polymer electrolyte membrane (PEM) fuel cell cathode and anode flow channels, respectively. Each flow channel is considered to be composed of two parallel walls, one porous (simulating electrode surface) and one non-porous, or impermeable, wall (simulating bipolar plate surface). Various flow situations have been analyzed, and the local and the averaged friction coefficient, Nusselt num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Koz and Kandlikar numerically calculated Sh FD to be 3.36 for a channel cross section of 0.40 mm × 0.70 mm. This Sh FD is significantly lower than the ones previously recommended: Sh FD =5.274 [42] (value readjusted for the characteristic length of hydraulic diameter), 6.0 [43], and 5.411 [44]. Moreover, it was shown that local Sh can be larger than Sh FD downstream of the droplet [41].…”
Section: Nomenclaturementioning
confidence: 57%
“…Koz and Kandlikar numerically calculated Sh FD to be 3.36 for a channel cross section of 0.40 mm × 0.70 mm. This Sh FD is significantly lower than the ones previously recommended: Sh FD =5.274 [42] (value readjusted for the characteristic length of hydraulic diameter), 6.0 [43], and 5.411 [44]. Moreover, it was shown that local Sh can be larger than Sh FD downstream of the droplet [41].…”
Section: Nomenclaturementioning
confidence: 57%
“…Analytical models were also developed to eliminate flow maldistribution for flow channels with and without considering reactant consumption. [9][10][11][12] More achievements of the flow field and channel geometries can be found in recent reviews. [13][14][15] However, most current design guidelines on flow channels are proposed based on the reactant flow behavior, but not involved in BPP manufacturability.…”
Section: Discussionmentioning
confidence: 99%
“…Roshandel et al optimized flow‐field design and channel configurations to achieve more uniform velocity distribution and more homogeneous molar spreading of species along the flow channels. Analytical models were also developed to eliminate flow maldistribution for flow channels with and without considering reactant consumption . More achievements of the flow field and channel geometries can be found in recent reviews .…”
Section: Introductionmentioning
confidence: 99%
“…Hassanzadeh et al [66] established a two-dimensional nonisothermal numerical model to solve governing equations of mass, momentum, energy, and species conservation for the developing laminar flow in cathode and anode flow channels of a PEM fuel cell. Each of the flow channels was regarded as two parallel planes with one porous plane (simulating electrode surface) and the other impermeable plane (simulating bipolar plate surface).…”
Section: Channel Configuration and Geometric Parametermentioning
confidence: 99%